2003
DOI: 10.1111/j.1471-0528.2003.02415.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress incontinence and pelvic floor neurophysiology 15 years after the first delivery

Abstract: Headline This is a longitudinal study of a cohort of primigravidae recruited between 1985 and 1987 and followed up 7 and 15 years later. Pelvic floor neurophysiology was performed and questionnaires were administered to determine the natural history of stress incontinence and to establish whether pelvic floor denervation after the first delivery is associated with symptoms of stress urinary incontinence in the future. Objectives To study the natural history of stress urinary incontinence arising during the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 16 publications
4
59
2
11
Order By: Relevance
“…In our study, most of the women reported a mild effect of UI on their quality of life. Some studies that have been conducted to evaluate the impact of UI in primiparous women reported a mild effect of UI in HRQL [27]. The impact on quality of life is considered to be mild, perhaps because most women consider urinary incontinence as a temporary difficulty that will resolve on its own.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, most of the women reported a mild effect of UI on their quality of life. Some studies that have been conducted to evaluate the impact of UI in primiparous women reported a mild effect of UI in HRQL [27]. The impact on quality of life is considered to be mild, perhaps because most women consider urinary incontinence as a temporary difficulty that will resolve on its own.…”
Section: Discussionmentioning
confidence: 99%
“…Having antenatal SUI doubles this risk. 28 Immediately after childbirth women may expect to have higher levels of incontinence, which can often resolve spontaneously over the first 6 months. As this natural resolution might confound the effect of any intervention, data from trials in women in the immediate postpartum period were not included in the main body of the systematic review or in the cost-effectiveness analysis (results are reported in Appendix 20).…”
Section: Postpartum Suimentioning
confidence: 99%
“…Sabe-se que a gravidez, o trabalho de parto e o parto podem provocar efeitos negativos na função dessa musculatura 20 e favorecer o aparecimento de IU em cerca de 38% das puérperas, porcentagem que se eleva para 45% em multíparas 21,22 . Isso justifica a importância dessa avaliação e de intervenção fisioterapêutica precoce, já que é uma abordagem de baixo custo, sem efeitos colaterais e tem demonstrado bons resultados.…”
Section: Conforme Recomendações Do Americanunclassified
“…Morkeved e Bo 25 demonstraram, em um seguimento de um ano, melhora significativa da força muscular do assoalho pélvico e diminuição da IU (p<0,01) em puérperas submetidas a um treinamento específico dessa musculatura. Como alguns estudos apontam possíveis disfunções perineais, especialmente após o parto vaginal 21 (tipo de parto mais comum na amostra estudada), os exercícios do assoalho pélvico são realizados de rotina, como medida preventiva, conforme recomendado pela literatura 18,25 . Algumas puérperas não realizaram os exercícios por apresentar desconforto na região da episiorrafia.…”
Section: Conforme Recomendações Do Americanunclassified